Analysis of fuzzy TOPSIS Method in Determining Priority of Small Dams Construction - Ulfiana, Desyta; Suharyanto, Suharyanto (Jurnal Teknik Sipil dan Perencanaan, 2019)
The limited government budget for the construction of small dam in Semarang Regency has led to the need to determine the construction priorities. However, the large number of construction's technical aspects causes the determination of the construction priorities to be difficult. One of the best methods for multi-criteria decision making is the Technique for Order Performance by Similarity to Ideal Solution (TOPSIS). However, ranking and weighting of the criteria that use in these constructions were difficult. It was caused by human assessment factors that were less precise especially on linguistic variables criteria. Therefore, a fuzzy logic was needed for calculating these criteria. There are eight alternatives of small dams and seven criteria of technical aspects analyzed in this study. The first step was determining membership function and weighting each criteria. Then, TOPSIS method was applied to ranked eight alternatives. The highest priority was determined by finding alternative that has the largest closeness coefficient (CCi). It represents alternative with closest distance to fuzzy positive ideal solution and farthest distance to fuzzy negative ideal solution. Based on analysis, Mluweh Dams has the highest CCi value of 0.612. It could be concluded that Mluweh Dams is the highest construction priority of small dams in Semarang Regency.